Creative Self-Perception of Spanish Secondary Teachers - Pont-Niclòs, Isabel; Echegoyen-Sanz, Yolanda; Martín-Ezpeleta, Antonio (Journal of Education Culture and Society, 2024)
Aim. The aim of this research is to analyse the creative self-perception of Spanish secondary teachers in different domains considering that creativity is increasingly being considered a key educational objective by organisations such as the Organisation for Economic Co-operation and Development (OECD) or educational laws, such as the recent Spanish one (Ministerio de Educación, Formación Profesional y Deportes Español, 2020).Methods. Participants were 100 Spanish in-service teachers at the level of secondary education. They completed the K-DOCS questionnaire (Kaufman, 2012), in which the self-perception of creativity in different domains (Self/Everyday, Scholarly, Performance, Scientific/Mechanic and Artistic) is assessed. The influence of variables such as gender, age, years of experience and area of teaching are analysed.Results. The analysis shows that Spanish secondary teachers have moderate-to-high perception of their own creativity. Although no statistically significant differences were found according to age or years of expertise, the scores in the Scientific/Mechanic domain were found to be significantly different according to gender. Separate creativity profiles were found for teachers with unrelated areas of expertise.Conclusion. This study aims to enhance understanding into the role of teachers in the promotion/hindering of creativity in classrooms. Results show a moderate creative self-perception with differences across domains, which logically conditions their conceptualisation of creativity and the importance given to it in classrooms. The importance of teacher training contributing to improve it is valued and key aspects are pointed out, such as the relevance of promoting a Centre Creative Plan with specific actions of a transdisciplinary nature in schools.